2016
DOI: 10.1016/j.jaip.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rhinosinusitis with Nasal Polyps

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is an important clinical entity diagnosed by the presence of both subjective and objective evidence of chronic sinonasal inflammation. Symptoms include anterior or posterior rhinorrhea, nasal congestion, hyposmia and/or facial pressure or pain that last for greater than 12 weeks duration. Nasal polyps are inflammatory lesions that project into the nasal airway, are typically bilateral, and originate from the ethmoid sinus. Males are more likely to be affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
330
3
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(371 citation statements)
references
References 84 publications
16
330
3
22
Order By: Relevance
“…A recent study indicated that AhR expression in allergic nasal mucosa was increased compared to that of normal mucosa [21], but there was lower expression in the atopic CRSwNP patients [11]. AR was associated with the recurrence of CRS [22] and there was a certain correlation between AR and CRSwNP [23]. In this study, the different AhR and TGF-β1 expression levels in CRSwNPwAR (i.e., decreased AhR expression and increased TGF-β1 expression) indicated that AhR might be affected by AR and other factors; however, the detailed regulation needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that AhR expression in allergic nasal mucosa was increased compared to that of normal mucosa [21], but there was lower expression in the atopic CRSwNP patients [11]. AR was associated with the recurrence of CRS [22] and there was a certain correlation between AR and CRSwNP [23]. In this study, the different AhR and TGF-β1 expression levels in CRSwNPwAR (i.e., decreased AhR expression and increased TGF-β1 expression) indicated that AhR might be affected by AR and other factors; however, the detailed regulation needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…AERD is present in about 7% of adult asthmatics and 14% of severe asthmatics (1) and may develop in patients without a prior history of atopy, asthma or rhinitis (2). The nasal polyps of AERD patients are intensely eosinophilic and contain activated mast cells (3, 4). The disease is characterized by release of large amounts of cysteinyl leukotrienes (CysLTs) and mast cells mediators, particularly prostaglandin D2 (PGD2), after COX-1 inhibitor ingestion (5, 6).…”
Section: Introductionmentioning
confidence: 99%
“…41,53 A healthy nasal epithelial barrier is known to be critical for protection against environmental factors, including allergens. 54,55 Other epithelial barrier indicators such as filaggrin (FLG), a member of the epidermal differentiation complex on chromosome 1q21, are reported to have polymorphisms and loss-of-function mutations associated with atopic dermatitis and AR. 53 It is well known that some inhaled allergens are proteinases that directly cause epithelial barrier dysfunction.…”
Section: Cell Polarization In Airway Epitheliummentioning
confidence: 99%